Analysis Of Social Media Utilization In Marketing Communication Implementation (Case Study On Sukokopi Jakarta) - Chance Ginaya Bancar; Sujoko Winanto (International Journal of Education, Information Technology, and Others, 2022)
Integrated Marketing Communication (IMC) are a communication strategy that is designed in such a way as to be specifically in accordance with the needs of targeted consumers. The use of social media as a IMC tool is one of the tools that is widely used to convey the company's message to its consumers. Sukokopi uses Instagram as the main social media in conducting marketing communications. This study contains an analysis of Instagram in the implementation of marketing communications on Sukokopi which has a humanist message by prioritizing local pride and Minang culture as the value of the coffee shop. This research uses qualitative methods with a constructivism paradigm. Researchers conducted interviews as a data collection technique and observed Sukokopi's Instagram. Interviews were conducted with 6 informants. The results of the research found that Sukokopi used various tools ranging from Insight as an initial analysis, Instagram ads, reels, posts in feeds and stories, interactive stickers, hashtags, and the nature of Instagram social media that is open and allows two-way communication. The message that Sukokopi wants to convey to its consumers is the comfort of the place and Minang culture as well as local coffee products that exist at the cafe. However, in delivering the message there is a gap where one of the messages, namely Minang culture, does not reach consumers completely. Sukokopi’s Instagram in Jakarta has a low level of activity and is less interactive. This causes a distant relationship between the company and consumers.